The experience of the older leisure traveller at an airport: the case of Frankfurt airport - Wolf, Natalie (2016)
This thesis is about the experience of older people who travel through an airport. The research reported took place at the interface of population ageing, tourism travel and airport management. Although air transport is influenced by population ageing, older people’s experiences within this specific environment are largely untold. This is surprising, as flying is the preferred form of travel for much of international tourism and airports represent key infrastructure for the provision of dependable services. Thus, there are gaps in knowledge on older travellers at an airport and the airport’s role in this part of leisure travel. In particular, a holistic examination of older travellers’ experiences within the airport environment is missing.